Meningkatkan Keterampilan Menanam Kunyit Melalui Metode Demonstrasi pada Anak Tunagrahita Ringan - Bayu Perdana Aryand; Fatmawati Fatmawati (Universitas Negeri Padang, 2019)
The purpose of this research is to describe the process of improving skills of planting saffron through the method of demonstrasion. Researcher used methods classroom action research. The results showed that planting turmeric learning through demonstration method is done in two cycles can be increased. Where the learning process carried out observations of teachers through observation guide format that initial activity. Results obtained final meeting of the second cycle that teachers obtain a value of 100%. The first cycle of four meetings and the second cycle of four meetings. It can be seen from the data before the given action, where the ability of the child while doing 16 steps to grow saffron namely: M is (55%), and O is (44%). While at the end of the first cycle capability M increased (70% ), and O (64%). In the second cycle capability M increased to (83% ), and O (83%).